Phase angle synchronization system of synchronous generators for parallel operation - V. V. Sushkov; E. E. Revyakin (Омский научный вестник)
In this paper, the synchronous generator shaftposition control system for synchronization process is explored. When the standard synchronization method is applied closing of a circuit breaker is accompany by the transient effects. This happens due to the voltage frequency of the synchronized generator is not equal to its synchronous value when the phase angle is controlled. The proposed synchronization approach allows to reduce the transient process influence on electrical equipment and improves the maneuverability of the control system in comparison with the standard method. Simulation modelling results are provided to illustrate it.